547. Results of Patient-Reported Outcome Data From the Phase III BRIGHTE Study of Fostemsavir. (26th November 2018) - Proudfoot, Clare; Ackerman, Peter; Llamoso, Cyril; Cella, David; Clark, Andrew; Murray, Miranda
Abstract: Background: The Phase 3 BRIGHTE study evaluated fostemsavir in heavily treatment experienced HIV-1 patients failing their current antiretroviral (ARV) regimen and unable to construct a viable regimen from remaining available agents. Week 24 efficacy and safety have been previously reported—fostemsavir resulted in virological and immunological improvements and was generally well tolerated. The objective of this abstract is to report analyses of patient-reported outcomes (PROs) from BRIGHTE. Methods: BRIGHTE included two cohorts: the randomized cohort (RC) had one to two classes of ARV therapy available; the nonrandomized cohort (NRC) had no ARV classes available. RC patients received fostemsavir or placebo + existing failing regimen for 8 days, and thereafter fostemsavir + optimized background therapy (OBT); NRC received fostemsavir + OBT throughout. PROs included the Functional Assessment of HIV Infection (FAHI), the EuroQol-5D-3L (EQ-5D) and associated visual analogue scale (VAS). Results: Both cohorts had advanced disease, low CD4 counts (median of 99.5 in RC and 41 in NRC) and high proportions of patients with AIDS (84% in RC and 90% in NRC). This was reflected in fairly low baseline FAHI scores. Improvements from baseline to Week 24 were observed in FAHI total score, physical well-being and emotional well-being subscales, with limited/no change in function/ global well-being, social well-being and cognitive function. Improvements in the RC were close to published values for minimum clinically important differences, with smaller improvements in the NRC. EQ-5D utilities were similar at Week 24 to baseline in both cohorts, with improvements in the EQ-5D VAS (11% in the RC, 8% in the NRC). Conclusion: The BRIGHTE study demonstrated improvements in PROs in heavily treatment experienced HIV patients, complementing previously published efficacy and safety results. Disclosures: C. Proudfoot, viiv healthcare: Employee, Salary. P. Ackerman, ViiV Healthcare: Employee, Salary. C. Llamoso, ViiV Healthcare: Employee, Salary. A. Clark, ViiV healthcare: Employee, Salary. M. Murray, Viiv healthcare: Employee, Salary.